Pembangunan Aplikasi Web Bantuan Kecemasan - Rosli, Muhamad Irham Firdaus; Mohd Yunus, Mohd Amin (Applied Information Technology And Computer Science, 2023)
Economic problems that hit us is one of the main challenges that the society must face. Among the organizations that are responsible for channeling aid to overcome this economic problem is JPKK Tanjung Minyak. However, the old methods used by JPKK Tanjung Minyak such as keeping notes in books and using WhatsApp applications to view and keep records of aid recipients slow down the provision of aid. People that want to provide help also need to go through a complicated process. The Emergency Aid Web Application System was developed to improve existing weaknesses. The main objective of the system developed is to ease users which is JPKK members, aid providers, aid recipients and system administrators. The Waterfall Model was chosen as the methodology of choice because the progress of the project is easy to monitor. The system was developed using Visual Studio Code, XAMPP and uses MySQL as the database. The development of this system can make the donation process run easily and in an orderly manner.